Sistem Monitoring Kecepatan dan Daya Mobil Listrik Pada IEMC (Indonesian Energy Marathon Challenge) - Eko Suryo, Arief Trisno; Mohamad Diki; Dwi Gita Anggagana (CV. Sekawan Siji, 2024)
This article discusses the speed and motor power monitoring system for IEMC electric cars. IEMC electric cars vary in speed and power when loaded, so the driver cannot know the speed and power produced. Furthermore, a monitoring system design is proposed to monitor speed and power when operating. The method uses a hall-effect-sensor to calculate voltage, current, power and speed and the monitoring system uses Xbee-Pro which is displayed on the monitor screen. Monitoring results show that without load it produces a current of 2.7-2.8 A, a voltage of 49.10-50.40 volts, a power of 129.10-136.08 watts. Meanwhile, an electric car with a load produces a current of 18.60-18.50 A, a voltage of 49.10-50.40 volts, and a power of 894.66-932.40 watts with a sensor distance of 0.5-1 cm each. Monitoring results show that voltage, current and power can be monitored via a PC or laptop in real-time.